2004
DOI: 10.1386/ltss.1.1.33/0
|View full text |Cite
|
Sign up to set email alerts
|

Student volunteering and the active community: issues and opportunities for teaching and learning in sociology

Abstract: Student volunteering is currently being promoted through the Higher Education Active Community Fund, which runs to August 2004 and may be extended further. This development of higher education's 'third mission' has strong links with the government's agenda for citizenship and the active community. This initiative appears to have taken little account of debates concerning both the ideological bases of volunteering, in particular the contested nature of citizenship and social capital, and the practicalities of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Most of the studies on student volunteering were undertaken in the United States, and to the best of our knowledge there is no data comparing student volunteering rates around the world. As a result, studies on student volunteering outside the U.S. still have to rely on the American example (see Hall et al 2004). For example, in Canada 33% of young people (aged 15-24) volunteer (Jones 2000), but the volunteering rate for students is unknown.…”
Section: Student Volunteeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies on student volunteering were undertaken in the United States, and to the best of our knowledge there is no data comparing student volunteering rates around the world. As a result, studies on student volunteering outside the U.S. still have to rely on the American example (see Hall et al 2004). For example, in Canada 33% of young people (aged 15-24) volunteer (Jones 2000), but the volunteering rate for students is unknown.…”
Section: Student Volunteeringmentioning
confidence: 99%
“…In the last five years, for example, the British government has encouraged students to volunteer through the Higher Education Active Community Fund. Most universities in the United Kingdom have a volunteer bureau and encourage students to volunteer, partly due to a much greater emphasis on employability in universities (Hall et al 2004). Organizations such as ''Student Volunteering England'' encourage a long-term commitment for British students (www.studentvol.org.uk).…”
Section: Introductionmentioning
confidence: 99%
“…The focus of the research reported below on the experience of volunteers may help to show the value of it The status of volunteering in English Higher Education (HE) has been strengthened in recent years, particularly through funding initiatives such as the Higher Education Active Community Fund which funded community engagement programmes in HE between 2002 and 2006. Volunteering has also been integrated in teaching programmes through the development of service learning programmes (Hall et al, 2004), while more generally volunteering is promoted as a way of enhancing students' career prospects' This is at the same time as getting involved in community activities (National Co-ordinating Centre for Public Engagement (NCCPE), 2009). A Scottish study showed that parents and guardians play a significant role in encouraging young people to volunteer, followed by teachers then friends (Volunteer Scotland, 2017).…”
Section: II Volunteering With Older Peoplementioning
confidence: 99%
“…In psychological well-being studies conducted on earthquake disaster volunteers in Pakistan, it was found that by volunteering, individuals feel there is a positive change from themselves, where they can be more respectful of themselves, others, life, feel close to God and feel the satisfaction in life (Najia, 2005). Hall, Hall, Cameron, Green (2004) also mentioned other positive impacts involved in joining volunteers such as gaining knowledge, improving social networks, and improving career prospects through voluntary activities.…”
Section: Introductionmentioning
confidence: 99%